Two new species of Evaniodes Szépligeti (Hymenoptera: Braconidae: Doryctinae) from French Guiana - Braet, Yves; Ceccarelli, Fadia Sara; Zaldívar-Riverón, Alejandro (Zootaxa, 2012)
Two new species belonging to the enigmatic doryctine genus Evaniodes Szépligeti, 1901 (Hymenoptera: Braconidae), E.palikuri Braet, Ceccarelli & Zaldívar-Riverón sp. nov. and E. wayampisi Braet, Ceccarelli & Zaldívar-Riverón sp. nov.,are described from French Guiana. Two of the three previously described species of Evaniodes, E. areolatus Szépligeti,1901 and E. spathiiformis Szépligeti, 1901, are recorded for the first time for French Guiana. A key to the five described species of the genus is provided.Deux nouvelles espèces du genre Evaniodes Szépligeti, 1901 (Hymenoptera, Braconidae), E. palikuri Braet, Ceccarelli &Zaldívar-Riverón sp. nov. et E. wayampisi Braet, Ceccarelli & Zaldívar-Riverón sp. nov. sont décrites de Guyane fran-çaise. Parmi les trois autres espèces d’Evaniodes connues à ce jour, E. areolatus Szépligeti, 1901 et E. spathiiformis Szép-ligeti, 1901 sont également signalées pour la première fois de cette région. Une clé d’identification des 5 espèces est fournie.